2014
DOI: 10.1242/jeb.105916
|View full text |Cite
|
Sign up to set email alerts
|

High fatty acid oxidation capacity and phosphorylation control despite elevated leak and reduced respiratory capacity in northern elephant seal muscle mitochondria

Abstract: Northern elephant seals (Mirounga angustirostris) are extreme, hypoxia-adapted endotherms that rely largely on aerobic metabolism during extended breath-hold dives in near-freezing water temperatures. While many aspects of their physiology have been characterized to account for these remarkable feats, the contribution of adaptations in the aerobic powerhouses of muscle cells, the mitochondria, are unknown. In the present study, the ontogeny and comparative physiology of elephant seal muscle mitochondrial respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 60 publications
3
32
1
Order By: Relevance
“…OXPHOS CI+CII capacity in penguin chicks was significantly lower than that of adults and those measured in our study animals. Our measured levels of OXPHOS CI+CII capacity in the duck thigh muscle were similar to levels measured in human vastus lateralis muscles (Chicco et al, 2014). Other studies examining metabolic enzyme development in skeletal muscles have revealed similar developmental trends as those shown here (e.g.…”
Section: Maturation Of Mitochondria Function Skeletal Musclesupporting
confidence: 88%
“…OXPHOS CI+CII capacity in penguin chicks was significantly lower than that of adults and those measured in our study animals. Our measured levels of OXPHOS CI+CII capacity in the duck thigh muscle were similar to levels measured in human vastus lateralis muscles (Chicco et al, 2014). Other studies examining metabolic enzyme development in skeletal muscles have revealed similar developmental trends as those shown here (e.g.…”
Section: Maturation Of Mitochondria Function Skeletal Musclesupporting
confidence: 88%
“…These data are congruent with previous reports of declining resting and submerged metabolic rates during the PWF (Rea and Costa 1992;Tift et al 2013), with a decrease in plasma LDH activity during the first 5 wk of fasting (Tavoni et al 2013), and with stable mitochondrial fat oxidation capacity during an ontogenetic decline in mitochondrial respiratory capacity in swimming muscle (Chicco et al 2014). The decrease in aerobic enzyme activities observed in this study may be an important component of development that underlies the low diving metabolic rates this species exhibits while foraging at sea (Maresh et al 2014).…”
Section: Changes In Muscle Enzymessupporting
confidence: 92%
“…In addition to large body oxygen stores, deep divers also exhibit reduced metabolic capacity in swimming muscles relative to athletic terrestrial mammals, which may enable maintenance of aerobic metabolism at a reduced level while diving (Reed et al 1994;Kanatous et al 2002;Chicco et al 2014). Juveniles of most phocids are not sufficiently developed at weaning to forage successfully and must undergo a developmental period to attain sufficient physiological capacity to support foraging (Thorson and LeBoeuf 1994;Noren et al 2003Noren et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Any samples showing a greater than 10% increase in respiratory flux under near-maximal OXPHOS states were excluded from the study. Muscles were dissected in ice-cold BIOPS and teased fiber bundles (5-8 mg) were permeabilized in BIOPS with 30 μg/ml saponin for 20 minutes, washed, and weighed as described (74). Mitochondrial respiratory function was measured in PMFBs by high-resolution respirometry using an Oxygraph-2K system (Oroboros Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…All respirometry data were collected at 37°C in a hyperoxygenated environment (250-400 μM O 2 ) to avoid potential oxygen diffusion limitations in PMFBs (75). Two titration protocols were run in parallel to measure mitochondrial function as previously described (74). For protocol 1, sequential additions of 5 mM pyruvate and 2 mM malate, 4 mM ADP, 10 mM glutamate, 10 mM succinate, 10 μM cytochrome c, 2 μg/ml oligomycin, followed by addition of the uncoupling agent carbonylcyanide p-trifluoromethoxy-phenylhydrazone (FCCP) in 0.5-μM steps, to each chamber.…”
Section: Methodsmentioning
confidence: 99%